Philippines private mailing cards & tarjetas postales, 1898-1903 - Luspo, Abraham Quisumbing Jr.; Verallo, Ma. Soledad Luspo ([Place of publication not identified] Chuchi Luspo Constantino, 2018)
These postcards are narratives of our history in pictures and words posted by those who dared to venture across oceans for their country, church, economic pursuits, and adventure. Many are beautiful and nostalgic especially the rare tarjetas postales which Abe designated as forerunners of the private mailing postcards the government began authorizing private printers to issue on May 19, 1898. These depict the local color and are highly prized and priced especially if stamped and postmarked. There is also a series of PMCs which are uniquely colored blue. My research to gather more information about these postcards was unsuccessful except for Mr. Heimfried Luers of The Public Album (TPA) in Germany who responded to my query about the tarjetas postales mailed from German ships. Although, tarjetas postales were originally issue in 1896 the focus of Abe's book is the picturesque postcards which were issued as early as 1898.

- Chuchi Luspo Constantino
FA-3594g - Donated by The family of the late author
Keywords: Postcards -- Philippines; Postcards -- Philippines -- Catalogs; Picture postcards -- Collections